A Study of Thyroid Profile in Patients with Benign Breast Disease (Anwer Khan Modern Medical College Journal, 2019)
Background: To observe the association between thyroid dysfunction and benign breast disease.Methods: Prospective observational study conducted in the surgical outpatient department on female patients with benign breast disease from April 2017 to April 2018.Results: Among the 208 female subjects included in the study 14.9% had hypothyroidism and 87.5% were completely symptom free when treated with Thyroxin replacement. Serum Prolactin level was also measured in all the subjects and hyperprolactinemia found in 4.8% with 50% associated with hypothyroidism.Conclusion: Thyroid profile may serve as a useful investigation in the treatment of patients with benign breast disease.Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 125-130